Incorporation of stable glycerol-borate complex into phenolic resin as a glue line treatment in engineered wood products. Issue 4 (3rd July 2020) - Currie, Robert B.; Byrom, Gary B.; Bruce, Alexander; Schmidt, Robert G.
ABSTRACT: A glycerol-borate complex has been developed and demonstrated as a new glue line treatment for engineered wood products such as laminated veneer lumber (LVL) and plywood. This allows the entire billet or panel to be evenly penetrated with boron to elevated levels, which increases the level in the central ninth and ensures the panel is significantly higher in boron throughout the panel compared with traditional envelope treatments. These external treatment systems often result in envelope treatments as it is difficult to get the treatment chemical evenly into the central ninth of the panel. The glycerol-borate complex reported herein is compatible with phenol formaldehyde resins typically used for plywood and LVL. These resins systems are not typically compatible with boron as the boron binds to the phenolic hydroxyl groups resulting in a range of undesirable side effects, such as premature gelation of the resin system. Boron is less toxic than alternative treatment chemicals and is very effective due to its broad spectrum of fungicidal and insecticidal activity. Boron does not break down into ineffective compounds and thus does not require high treatment dose levels. Additionally, the amount added can be directly measured using ICP-MS to ensure a suitable level of treatment chemical has been added.